Children with Long Covid: Co-producing a specialist community public health nursing response. (2nd October 2021) - Fanner, Michael; Maxwell, Elaine
Abstract : Globally, children have been profoundly affected by the Covid-19 pandemic in many ways. While the majority of children with acute Covid-19 infection experience mild illness and fully recover, many go on to experience Long Covid. Long Covid is clinically identified by experience of persistent (and sometimes different) symptoms for several months after the acute infection (even in children who were asymptomatic). There is currently no agreed consensus on the case definition of Long Covid, but real-world data from American health insurance firms and the UK Office for National Statistics report that children may experience intestinal symptoms, pain, breathlessness, cognitive dysfunction and post-exercise malaise. The current understanding of the natural history, diagnostics and treatments of Long Covid is limited, meaning the medical model in isolation is not helpful. Health visitors and school nurses are ideally placed to case-find children with Long Covid and co-produce child and family-centred care.